The Urgency of Rehabilitation in the Utilitarian Paradigm to Punishing Narcotics Addicts - Muhammad Ridwan Lubis; Cut Nurita; Dian Pramana; Diana Lubis (Unissula, 2023)
Rehabilitation for narcotics abusers is a recovery method that needs to be carried out by prisoners who are categorized as addicts and victims of narcotics abuse. Rehabilitation is part of the use of utilitarian principles. The purpose of this research is to analyze the urgency of implementing rehabilitation for drug addicts and to analyze the rehabilitation of narcotics addicts in the utilitarian paradigm. This research is a type of normative juridical research to examine the urgency of implementing rehabilitation for narcotics addicts in a utilitarian paradigm. Even though articles regarding the implementation of rehabilitation have been regulated, enforcement of the law remains rare, creating the impression of selective logging in its implementation. Therefore, it is essential to scrutinize whether the implementation of rehabilitation for narcotics users aligns with the provisions of the Narcotics Law and the norms outlined in the relevant articles. The benefits that people with drug addiction get from rehabilitation are in the form of detoxification and social rehabilitation, which are designed to facilitate the user's reintegration into regular life, along with the following stages of treatment. Thus, regarding the benefits for the Indonesian state, providing rehabilitation for narcotics addicts is believed to be able to reduce the number of narcotics trafficking itself.